2017
DOI: 10.1177/2167702617709560
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Mental Disorders Is Influenced by Automatic Causal Reasoning

Abstract: , which mirrors the DSM, provide normative frameworks for the diagnosis of mental disorders. Classifications are supposed to be based on diagnostic criteria, most of which are neither necessary nor sufficient. These diagnostic criteria are usually directly observable symptoms. Neither of the two classification systems is based on causal, etiological theories of mental disorders. Potential causal relations between the symptoms listed as criteria are not included in the definition. This means that clinicians sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Limitations in prototype approaches to diagnosis notwithstanding (see Spitzer, First, Shedler, Westen, & Skodol, 2008), PDM descriptions dovetail with how clinicians process and encode information. As Flores et al (2017) have shown, when thinking about patients, clinicians do not generate symptom lists, but tend to perceive and classify patients with respect to how well they match exemplars of similar patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations in prototype approaches to diagnosis notwithstanding (see Spitzer, First, Shedler, Westen, & Skodol, 2008), PDM descriptions dovetail with how clinicians process and encode information. As Flores et al (2017) have shown, when thinking about patients, clinicians do not generate symptom lists, but tend to perceive and classify patients with respect to how well they match exemplars of similar patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the theoretical and empirical literature describes case formulation as a deliberate, mindful process—which it is—it is important to recognize that all clinicians reflexively conceptualize the core features of newly encountered patients based on past experiences with other similar patients, even when they are not consciously aware of doing so (Flores, Cobos, & Hagmayer, 2017; Westen & Weinberger, 2004). Put another way, an initial case formulation inevitably occurs implicitly, and when it does it is tainted by all sorts of biases and distortions (e.g., stereotypes, heuristics, attribution errors; see Bornstein, 2017; Croskerry, 2016).…”
Section: Implicit and Explicit Case Formulationmentioning
confidence: 99%
“…Response latency is a potential operational definition of which system a clinician uses for a diagnostic decision (e.g., Flores, Cobos, & Hagmayer, 2018). Faster response times would indicate the use of System 1, where slower response times would imply the use of System 2.…”
Section: Diagnostic Decision Makingmentioning
confidence: 99%
“…We used mediation models to determine whether clinician characteristics influence diagnostic accuracy through response time. Based on past research, it was hypothesized that clinicians with more experience would respond quicker and provide more accurate diagnoses (Croskerry & Nimno, ; Flores et al, ). In addition, we hypothesized that clinician profession would influence diagnostic accuracy through differences in response time.…”
Section: Current Studymentioning
confidence: 99%
“…The stimuli used in the first five articles are suitable for empirical research. In four of the five studies, they are vignettes (also called short clinical reports) of real disorders (Flores, Cobos, & Hagmayer, 2018 [this issue]; Marsh & De Los Reyes, 2018 [this issue]; Weine & Kim, 2018 [this issue]) or fictitious diseases (Hayes, 2018 [this issue]). Such stimuli approximate what clinicians will see in practice and allow the researcher to manipulate the relevant variables.…”
Section: Clinical Decision-making Researchmentioning
confidence: 99%